KEMAMPUAN SISWA SMA DALAM MENYELESAIKAN SOAL UNFISIKA BERDASARKAN TAHAPAN MODEL IDEAL PADA MATERI LISTRIK STATIS - Fitiria Wahyu Maharani; Singgih Bektiarso; Trapsilo Prihandono (FKIP Universitas Jember, 2018)
Abstract Physics learning is an effort to improve problem solving ability. This studyaimed at determining high school students’ ability in solving the physics nationalexamination problem based on the stages of IDEAL model on static electricitymaterials. By knowing that ability, it can be a motivation to improve problem solvingability of physics national examination to obtain better results. The research methodused is descriptive qualitative. The subjects of this study is last year students of SMAAmbulu and SMAN Balung. Based on this research, we can know the student’s abilityon identify the problem stage in SMAN Ambulu and SMAN Balung was categorizedas very good of 95.60% and 85.90%. The define represent the problem wascategorized as very good and good of 93.54% and 82.14%. The explore possiblestrategies stage in SMAN Ambulu was categorized as very good by 87.74%, while inSMAN Balung was categorized as sufficient of 68.88%. The act on the strategiesstage in SMAN Ambulu was categorized as very good, and in SMAN Balung wascategorized as good. Whereas, the look back and evaluate the effect stage in SMANAmbulu and SMAN Balung was categorized as good of 74.26% and 50.52%.Key words: Physics, IDEAL model, solve problems